Analysis of the Potential for Revitalization of Modern Markets (Mall) in Gresik Indonesia (International Journal of Scientific Research and Management (IJSRM), 2022)
the covid-19 pandemic that is endemic in Indonesia requires large-scale social restrictions so that all activities are carried out online (in the network), one of which is buying and selling activities. This condition causes a decline in the regional and national economy. Many retail markets and modern markets (malls) are empty of visitors until they are out of business. This condition also occurs in the urban area of ​​Gresik Regency, so that it becomes the research location. The long-standing social distancing policy in Gresik Regency has resulted in the Hypermart modern market going out of business, and Ramayana experiencing a significant decline in visitors. This condition causes the Hypermart modern market building (mall) to become an area of ​​lost space which actually has a bad impact on the visuals of urban areas. The development of urban areas has led to the development of modern markets (malls) with a regional service scale. This condition causes the need for a review if it is going to restore the function of the modern market (mall) Ramayana and Hypermart to the fullest. This research was conducted by looking at the service coverage of the two malls, using network analysis. The data used are road network data, house parcels and the location points of each modern market (mall). The analysis carried out provides information that there is considerable potential if the Hypermart and Ramayana modern markets (malls) are again functioned as shopping places with a community service scale. However, it is necessary to differentiate between the two in order to form different market segments.